Aspirazioni e aspettative lavorative: giovani studenti italiani e stranieri a confronto - Debora Mantovani (Quaderni di Sociologia, 2013)
This paper presents results from a survey conducted in upper secondary schools of Bologna aimed at exploring the trajectories leading young students to the working world. The survey was conducted in the 2009/10 school year by means of a questionnaire administered to 1,080 students (577 non-Italians). A job is still a distant goal for most 15-year-old students. Nonetheless, it is important to investigate if, and to what extent, teenagers think about their occupational future and what their actual job aspirations are. More precisely, the paper aims to examine the degree of consistency between job aspirations and realistic expectations, paying particular attention to the probable differences existing between Italians and non-Italians, and the relationship between this consistency and social class of origin.The comparison between females and males reveals greater differences than the comparison between non-Italian and Italian students in terms of occupational aspirations and actual career plans. As regards their occupational aspirations Italians are as likely to be “dreamers” as their non-Italian schoolmates, and both groups of students are much more “pragmatic” if they refer to their realistic job opportunities. Social class influences occupational expectations to a greater degree than aspirations, and foreign students show higher social mobility expectancy than Italians.